(untitled) (Journal of Geography and Environmental Management, 2017)
Because of the wide use of radioactive substances there is a threat of soil contamination with radionuclides. Sources of radiation – nuclear facilities, nuclear weapons testing, uranium mine waste. Potential sources of radioactive contamination are accidents at nuclear installations. In the upper soil layer and concentrate radioactive cesium and strontium, which enter the body of humans and animals. The accumulation of radionuclides in the environment in large quantities can lead to tragic situations. A large part of the radionuclides are in the soil, in its upper and lower layers, so their movements largely depends on the types of soils, their granulometric composition and water-physical and agrochemical properties. The transfer speed depends on hydro-meteorological effects (wind speed and intensity of precipitation), topography, terrain, type of soil and plants and physico-chemical properties of the nuclides. Therefore it is necessary to carry out radiation monitoring of the environment. The article presents the results of a study of background radiation and the specific activity of the isotope cesium-137 near the industrial enterprises of Uralsk. The studies were conducted for each season of the year. The proposed pattern of change of the specific activity of the isotope cesium-137 in air, water, soil, plants nearby businesses.